Pemetaan Potensi Karbon di Lahan Gambut Topogen Pada Berbagai Kecamatan di Kabupaten Humbang Hasundutan, Provinsi Sumatera Utara - Grandis Tua Sitanggang; Rahmawaty Rahmawaty; Abdul Rauf (Peronema Forestry Science Journal, 2013)
Mapping the potential of carbon was an inventory activities that the carbon content and deposits can be mapped and known. Mapping the potential of carbon would provide information that will be useful in the management of peatland resources. The objective of this study was to map peatland area, know the type of land cover and know the amount of carbon stored in the peat. This research method was the analysis of Landsat ETM + image data of 2012, field measurements and sampling and soil analysis results of field measurements. The results showed the whole area of ​​peatland was 6289.08 ha or about 2.513% of the total land Humbang Hasundutan district. Land cover types are rice peat, peat swamp forests, non-vegetation, shrubs peat, peat mining areas, and coffee farming. Total carbon content in peat Humbang Hasundutan District of 170,45 tonnes. Peatland management should be done by considering the carrying capacity and environmental sustainability, in order to obtain benefits not only on the environment but also on the social and economic community. Keywords: Potential Carbon, Topogen Peat Land, Peat Land Carbon Mapping